The ASEAN Economic Community and the Philippines: Implementation, Outcomes, Impacts, and Ways Forward (Integrative Report) - Melanie S. Milo (Philippine Institute for Development Studies (PIDS), 2013)
As 2015 draws near, assessing ASEAN's progress toward the ASEAN Economic Community (AEC) defined by the AEC Blueprint is necessary and instructive. This paper constitutes the Mid-Term Review (MTR) of the AEC Blueprint for the Philippines. The Philippines Country Report presents the results of the surveys related to the MTR on areas including trade liberalization and facilitation, services and investment liberalization, labor mobility, and agriculture. In assessing the progress of implementation of the country's commitments under the AEC, a scorecard mechanism is applied. The report also covers two case studies as well as discussions on the role of the private sector and SMEs, and concludes with recommendations to raise the implementation rate of the AEC measures in the country.Overall, the survey results demonstrate how the AEC and the AEC Blueprint could address some of the issues that have constrained private sector response to the opportunities provided by greater openness in the Philippines, particularly the complex and inefficient administrative processes and procedures, and lack of effective competition in key sectors of the economy. While the Philippines has demonstrated its commitment to the AEC and the AEC Blueprint, key measures still need to be realized, particularly those that relate to services liberalization, customs integration, and ratification of transport protocols and agreements. The analyses of the study have demonstrated the benefits of the accomplishment of AEC measures in the Philippines, particularly those that precisely addressed the key institutional weaknesses faced by the private sector. Further delays in implementation could be costly for the country.
Keywords: 330; labor mobility; Philippines; agriculture; investment facilitation; ASEAN economic integration; AEC scorecard; services liberalization; standards and conformance